Mixing Urea and Zeolite for Slow Release Fertilizer using Orbiting Screw Mixer - Semuel Pati Senda; Renanto Handogo; Achmad Roesyadi; Wahono Sumaryono (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2009)
Slow release fertilizer (SRF) of urea is prepared by using zeolite as the matrix. Mixing of urea and zeolite is carried out in orbiting screw mixer. The effects of rotation speed and orbital speed of the mixer and particle size on power consumption, homogeneity, mixing time and specific energy consumption are evaluated. The experimental results show that higher orbital speed gives higher power consumption. Power consumption is dominated by mixer rotation motion. Smaller particle size needs higher power for mixing process. Nitrogen mass fraction ranges from 0.45 to 0.49 when mixture reaches homogeneity. The mixing time required is about 5 – 12 minutes for particle size of >60 and >80 mesh and 7 – 14 minutes for particle size of >50 mesh. At constant orbit speed, the higher the screw rotation speed, the shorter time needed to reach mixture homogeneity. Specific energy consumption of mixing process increases with decreasing particle size. For the three particle size groups of >80 mesh, >60 mesh and >50 mesh, the lowest specific energy consumption is given by combination of orbital speed of 5 rpm and rotation speed of 50 rpm; while for particle size of >60 mesh and >80 mesh, it can obtained by combination of orbital speed of 5 rpm and rotation speed of 67,5 rpm and orbital speed 5 rpm and rotation speed 30 rpm, respectively. The lowest specific energy consumptions is gained by combination of orbital and rotation speeds of 5 and 50 rpm with particle size of >50 mesh.